Enviromental Civic Engagement in the Community Parit Tokaya Village through Rosella Waste Bank - Hayati Hayati; Sulistyarini Sulistyarini; Jagad Aditya Dewantara; Afandi Afandi; Efriani Efriani (JED (Jurnal Etika Demokrasi), 2024)
The problem of this research is environmental problems, especially waste that cannot be handled properly. This is aims to determine the resolution of waste problems through forms of civic engagement in the environmental field in the Parit Tokaya Village community at the rosella waste bank. This research uses a case study method conducted at the rosella waste bank. The results of the research findings show that solving waste problems through forms of civic engagement in the environmental field in the community at the rosella waste bank is carried out through various activities. These activities include sending and collecting waste to the rosella waste bank, sorting waste, making crafts from used goods, campaigning for environmental care, and socialising about waste to the community and schools. The rosella waste bank succeeded in reducing waste problems by involving the Parit Tokaya Village community.